Analisis Sarana Dasar Kesehatan Lingkungan yang Berhubungan dengan Kejadian Diare pada Anak Balita di Kecamatan Gading Cempaka Kota Bengkulu - Fauzi, Yusran; Setiani, Onny; Raharjo, Mursid (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2005)
ABSTRACT Backgroud : Diarrhea still represent the problem in Indonesia with the morbidity rate is about 20-40% and the mortality rate is 134 per 100.000 on children under five years. This research aim was to determine the correlation between basic infrastructure of environmental health and the diarrhea incidence on children under five years. Method : This Research was carried out in Sub district Gading Cempaka, Bengkulu City by using the Case-Control design with the analytic survey method to 120 respondents of mother who have children under five years, consisted of 60 cases and 60 controls. The independent variable was basic infrastructure of environmental health include fresh water infrastructure type, the risk level of fresh water source contamination, fresh water quantity, fresh water bacteriological quality, latrine type, latrine condition, sewage disposal infrastructure type, sewage disposal infrastructure condition, waste disposal type, waste disposal condition and the dependent variable was diarrhea incidence on children under five years. Chi-Square test and multiple logistics regression test was used to determine the corrrelation between basic infrastructure of environmental health and the diarrhea incidence on children under five years. Result : The Result found significant correlation between the infrastructures of environmental health variable and diarrhea incidence on children under five years. Conclusion : It concluded that, there are strength correlation between the level of fresh water source contamination (OR=6,196; 95% CI 2,321-16,537), latrine type (OR=3,268; 95% CI 1,221-8,749) fresh water infrastructure type (OR=3,376; 95% CI 1,162-9,084) and diarrhea incidence on children under five years in Subdistrict Gading Cempaka, Bengkyulu City. Keywords : Basic infrastructure of environmental health, Diarrhea, Children under five years.